Knowledge, attitudes, and perception of prostate cancer among male outpatients of a tertiary care hospital in south-east Nigeria - Deborah O. Aluh, Obinna C. Anyachebelu, Ekwuofu Amos Azubuike, Isah Abdulmuminu (Journal of Applied Pharmaceutical Science, 2018)
Prostate cancer is the number one cancer in males both in incidence and mortality in Africa and the increased mortality rate amongst this population is mainly attributed to late presentation. It has been postulated that poor perceptions and knowledge about prostate cancer and the availability of alternative therapies are the reasons for late presentation. This study seeks to find out if the media attention and increased awareness of prostate cancer in Nigeria has actually improved the knowledge and attitudes of men toward prostate cancer. The study was a cross-sectional descriptive study conducted among men aged ≥18 years in the General Outpatient Department of Chukwuemeka Odumegwu Ojukwu University Teaching Hospital. The mean percentage knowledge score was 60.29%. The mean percentage attitude score was 60.79%. The mean percentage perception score was 66.82%. Less than half of them (43.3%) had a positive attitude toward prostate cancer. More than half (53.6%) of them had a negative perception of prostate cancer. There was a strong evidence of association between education and perception of prostate cancer (X2 = 20.14, p = 0.000). In conclusion, the patients of the hospital expressed a reasonable level of knowledge about the prostate cancer.
Keywords: Prostate cancer, knowledge, attitude, perception, Nigeria, outpatients.